Efektivitas Psikoedukasi Wawasan Kebangsaan untuk Menurunkan Kecenderungan Radikalisme pada Mahasiswa - Ariyanto, Eko April; Haque, Sayidah Aulia Ul; Syafii, Achmad Rizal (Philanthropy: Journal of Psychology, 2019)
This research is motivated by the growing understanding of radicalism in Indonesia, including among the young generation of Indonesia. The younger generation should be the hope of the nation to continue the struggle of the predecessors to advance Indonesia, but if the young generation has been exposed to radicalism, it is necessary to provide an intervention in this case in the form of psychoeducation. The purpose of this study was to determine the effect of "Nationality Insight" psychoeducation on the emergence of radicalism in students. This study uses a comparative quantitative approach with data collection using non-probability sampling techniques in the population at the University August 17, 1945. The results of the Paired Sample T Test obtained significance of 0.104> 0.05. The results of the Paired Sample T Test on the pre-test and post-test scales in the group treated in the form of Nationality Psychoeducation obtained a significance of 0,000 <0.05. The results of this study prove that the "National Insight" psychoeducation method is effective in reducing the attitude of radicalism to students. Keywords: National Insight, Radicalism, Students Daftar Pustaka Aly, Abdul, (2011). Pendidikan Islam Multikultural di Pesantren, Yogyakarta: Pustaka Pelajar. Ancok, D. (2008). Ketidakadilan Sebagai Sumber Radikalisme dalam Agama: Suatu Analisis Berbasis Teori Keadilan dalam Pendekatan Psikologi. Jurnal Psikologi Indonesia 2008, No. 1, 1-8, ISSN. 0853-3098 Cross, R. (2013). Radicalism. dalam Snow, D., della Porta, D., Klandermans, B., dan McAdam, D. (eds.). The Wiley-Blackwell Encyclopedia of Social and Political Movements. doi: 10.1002/9781405198431.wbespm175 Departemen Pendidikan Nasional. (2002). Kamus Besar Bahasa Indonesia ed. III. Jakarta: Balai Pustaka Diktis.kemenag.go.id/NEW/index.php?berita=detil&jenis=news&jd=162.#.XeyoM25uLtQ. Diakses pada tanggal 8 Desember 2019 Endang Turmudi, Riza Sihbudi. (2005). Islam dan Radikalisme di Indonesia. Jakarta: Lembaga Ilmu Pengetahuan Indonesia Hasyim, M., dkk (2015). Diskursus Deradikalisasi Agama: Pola Resistensi Pesantren terhadap Gerakan Radikal. Jurnal Penelitian Sosial Keagamaan. UIN Wali Songo Kolb, D. (1984). Experiential Learning: Experience as the Source of Learning and Development. Latipun. 2004. Psikologi Eksperimen. Malang: UMM Press McCauley, C. dan Moskalenko, S. (2008). Mechanisms of Political Radicalization: Pathways Toward Terrorism. Terrorism and Political Violence, 20:3, 415-433. doi: 10.1080/09546550802073367 Moskalenko, S. dan McCauley, C. (2009). Measuring Political Mobilization: The Distinction Between Activism and Radicalism. Terrorism and Political Violence. 21:2, 239-260. doi:10.1080/09546550902765508 Nelson-Jones, R. (1982). The theory and practice of counselling psychology. London: Holt, Rinehart and Winston Rahimullah, Riyad Hosain, Setephen Larmar, and Mohamad Abdalla. (2013). € Radicalization and Terrorism: Research within the Australian Context. €ŸInternational Journal of Criminologyand Sociology. Vol. 2. Hlm 180-185. Saifuddin, (2011). Radikalisme Islam di Kalangan Mahasiswa. Jurnal Studi Keislaman Vol. XI No. 1 (Juni, 2011), 28. Salehuddin, A. (2012). Understanding Religious Violence In Indonesia: Theological, Structural and Cultural Analyses. Journal of Indonesian Islam. UIN Sunan Ampel Surabaya Seniati dkk. (2005). Psikologi Eksperimen. Jakarta: PT. Indeks Taylor, D. C. M., & Hamdy, H. (2013). Adult learning theories: Implications for learning and teaching in medical education: AMEE Guide No. 83. Medical Teacher, 35(11), e1561 e1572. https://doi.org/10.3109/0142159X.2013. 82815